2018
DOI: 10.5604/01.3001.0012.3141
|View full text |Cite
|
Sign up to set email alerts
|

A Head CT is Unnecessary in the Initial Evaluation of A Cirrhotic Patient with Recurrent Hepatic Encephalopathy

Abstract: In conclusion, the yield of a head CT in determining the cause of change in mental status is extremely low in patients with cirrhosis who present with recurrent hepatic encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…These two patients had a 5 mm haemorrhagic metastatic lesion and an 8 mm cortical haemorrhage, both without mass effect or surrounding oedema. Similarly, Kumar et al evaluated 147 HCTs in cirrhotic patients presenting with HE, in which 4% had abnormal HCT findings 6 and only one (0.7%) patient had abnormal imaging in the setting of a normal neurological exam. However, the patient did have a history of remote fall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These two patients had a 5 mm haemorrhagic metastatic lesion and an 8 mm cortical haemorrhage, both without mass effect or surrounding oedema. Similarly, Kumar et al evaluated 147 HCTs in cirrhotic patients presenting with HE, in which 4% had abnormal HCT findings 6 and only one (0.7%) patient had abnormal imaging in the setting of a normal neurological exam. However, the patient did have a history of remote fall.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patient did have a history of remote fall. 6 All patients in Rahimi and Rockey’s cohort evaluating cirrhotic patients admitted to the hospital with altered mentation found to have abnormal imaging had FNDs. 7 Lastly, Donovan et al examined a cohort of patients with cirrhosis presenting with HE and reported higher rates of detecting ICH in patients presenting with trauma, FNDs or a history of ICH compared with patients presenting with AMS, headache or fever.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicians may have concern regarding intracranial hemorrhage due to underlying coagulopathy or thrombocytopenia, even though these findings do not translate to an increased risk of bleeding [3,12]. Studies have shown that the yield of brain imaging in repeat HE admissions is low, specifically when there are no histories of falls or trauma or focal neurologic deficits on exam [5,13]. Donovan et al looked at 462 HE admissions and found that the number needed to scan (NNS) for a positive result varied by indication for the scan, showing a low yield if no indication for imaging other than altered mental status: focal neurological deficits (NNS � 9), fall/trauma (NNS � 20), and altered mental status without any other findings (NNS � 293) [14].…”
Section: Discussionmentioning
confidence: 99%